Seleksi dan Konfirmasi Alel Gen-gen Hd pada Padi Berumur Genjah dan Produktivitas Tinggi Persilangan Code x Nipponbare - Ahmad Dadang; Tasliah Tasliah; Joko Prasetiyono (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2013)
To support the IP 300 program rice varietieswith both early maturity and high productivity are needed.The objective of the research was to improve those traits inCode variety using RIL (recombinant inbreed line) methods.The research was conducted in the year 2009-2011 at thegreenhouse and laboratory of Molecular Biology, IndonesianCenter for Agricultural Biotechnology and GeneticResources Research and Development. Materials consistedof 600 individuals of F2 derived from one of F1 Code xNipponbare crossed plants and they were planted up to F4with seed-to-seed, then confirmed by 8 microsatelitemarkers linked to loci of Hd genes. The molecular analysisshowed that 84 of 600 F2 plants produced. The F4 plants have50% of flowering time shorter than F2 and F3 plants. Twolines (CdNb_388 and CdNb_270) have higher productivitycompared to Code by the number of productive tillers (20)and the number of tiller grains (2240 and 1740) and haveclosely 50% of 60 days flowering time of Nipponbare. Threelines of F4 plants (CdNb_270, 364, and 388) were predictedto have allele of Hd7 gene, and CdNb_472 was predicted tohave alelle of Hd14 gene.